2009
DOI: 10.1063/1.3273326
|View full text |Cite
|
Sign up to set email alerts
|

CO chemisorption on the surfaces of the golden cages

Abstract: We report a joint experimental and theoretical study of CO chemisorption on the golden cages. We find that the Au 17 − cage is highly robust and retains its cage structure in Au 17 ͑CO͒ − . On the other hand, the Au 16 − cage is transformed to a structure similar to Au 17 − upon the adsorption of CO. Au 18 − is known to consist of two nearly degenerate structures, i.e., a cage and a pyramidal isomer, which coexist in the cluster beam. However, upon CO chemisorption only the cage isomer is observed while the py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 64 publications
0
38
0
Order By: Relevance
“…Since simulated PES spectra with the inclusion of SO effects have not been reported for gold clusters in the size range of Au 9 − -Au 12 − , they are presented here as references. We have found that the inclusion of SO effects can yield simulated PES spectra in much better agreement with the experimental PES data, 42,57 making it possible to identify structures with much higher confidence on the basis of the simulated PES spectra. This is important because of the limited accuracy in the DFT-based energetic information among closely lying structural isomers.…”
Section: Theoretical Results and Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Since simulated PES spectra with the inclusion of SO effects have not been reported for gold clusters in the size range of Au 9 − -Au 12 − , they are presented here as references. We have found that the inclusion of SO effects can yield simulated PES spectra in much better agreement with the experimental PES data, 42,57 making it possible to identify structures with much higher confidence on the basis of the simulated PES spectra. This is important because of the limited accuracy in the DFT-based energetic information among closely lying structural isomers.…”
Section: Theoretical Results and Discussionmentioning
confidence: 64%
“…We recently found that the inclusion of spin-orbit ͑SO͒ effects 56 is essential to achieve quantitative agreement between simulated and measured photoelectron spectra for Au clusters. 42,57 In the current work, we used the PBE0 hybrid functional and CRENBL basis set ͑i.e. the large effectivecore-potential orbital basis for use with the small core poten-tials͒ including SO effects, as implemented in NWCHEM 5.1.1, 58,59 to calculate the photoelectron spectra of the lowlying isomers.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…Nevertheless, a definitive proof on the existence of an HGC conformation with more than 20 atoms remained elusive, particularly, among charged gold clusters. Among the neutral clusters, two HGC conformations, viz., Au 18 and Au 32 are widely studied for their potential electronic and catalytic properties [35][36][37][38][39][40]. These studies validate that both the HGCs are excellent red-ox agents and can be even an eminent choice for the selective oxidation of styrene to benzaldehyde [37].…”
Section: Introductionmentioning
confidence: 88%
“…Because of the strong relativistic effects of the gold atom, the spin orbit (SO) coupling effect [74] also must be considered for heavy atoms such as gold. The PBE0/CRENBL level and SO effects were carefully selected for the gold atom to achieve quantitative agreement between the experimental and theoretical PES spectra [64,[75][76][77][78][79].…”
Section: Theoretical Methodsmentioning
confidence: 99%